PENGARUH PENGAWASAN DAN SEMANGAT KERJA TERHADAP EFEKTIVITAS KERJA KARYAWAN PT. MULTI ARTHA UNIVERSINDO MEDAN - Wily Julitawaty; Rinaldi; Thomas Sumarsan Goh (JURNAL BISNIS KOLEGA, 2018)
The success and progress of the company is strongly influence by human resources that exist within the company. For the good quality of human resources, the company must apply good monitoring and improve job enthusiasm to makes job effectiveness better in future. The purpose of this study was to determine the influence of monitoring and job enthusiasm toÂ  job effectivenessÂ  at PT. Multi Artha Universindo Medan.The analysis methods used in this research are quantitative analysis. The data used in this researchwere primary data and secondary data. The population of this research is 34 peoplesand the sampling is using saturation sampling technique in which all members of the population become samples. The variables were measured by Likert scale. Data analysis technique in this research is multiple linear regressions.The results of this research stated that simultaneously monitoring and job enthusiasm are influencing job effectiveness at PT.Multi Artha Universindo Medan. Partially, monitoring is influencing job effectiveness and job enthusiasm is influencing job effectivenessat PT.Multi Artha Universindo Medan. Key Words : Monitoring, Job Enthusiasm, Job Effectiveness